2012
DOI: 10.1159/000336736
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Post-Stroke Fatigue: The Fatigue Scale for Motor and Cognitive Functions

Abstract: Background/Aims: Post-stroke fatigue (PSF) is an important but still controversial issue since knowledge on its nature is still humble. The aim of the present study was to characterize PSF beyond the subacute phase. Methods: Thirty-one stroke patients (gender: 6 female, 25 male; age range: 35–76 years; 28 patients with ischemic stroke, 3 patients with hemorrhagic stroke; mean delay after stroke: 50.65 ± 31.57 days) were recruited and assessed by measures of fatigue (Fatigue Scale for Motor and Cognitive Functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 47 publications
0
51
0
Order By: Relevance
“…The relationship between these outcomes provides further evidence that perceptions of fatigue and measures of executive control may be related (61, 62). Previous studies that demonstrated a similar relationship between subjective ratings of fatigue and performance on measures of executive functions (63, 64) were limited to populations with MS (64, 61) or a history of stroke (63). The current study extends these findings to a healthy, community-dwelling, aging population.…”
Section: Discussionmentioning
confidence: 95%
“…The relationship between these outcomes provides further evidence that perceptions of fatigue and measures of executive control may be related (61, 62). Previous studies that demonstrated a similar relationship between subjective ratings of fatigue and performance on measures of executive functions (63, 64) were limited to populations with MS (64, 61) or a history of stroke (63). The current study extends these findings to a healthy, community-dwelling, aging population.…”
Section: Discussionmentioning
confidence: 95%
“…Cognitive impairment is a common sequela following stroke (Douiri et al, 2013). Screening for mild cognitive impairment was completed using the MMSE (Folstein et al, 1975) with both groups demonstrating a similar reduction in cognition, although lower than average scores may reflect a degree of cognitive fatigue that is often seen in the subacute stroke phase (Hubacher et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…A cross-sectional study showed that attention deficits are associated with PSF. 22 Others found that processing speed was correlated with mental fatigue at 3 and 6 months after stroke 34,83,84 and that memory dysfunction was related to PSF at 6 months after stroke. 34 Thus, although PSF is not likely to be associated with general e162 Stroke July 2017…”
Section: Cognitive Impairmentmentioning
confidence: 99%